Cardiorespiratory fitness in children and adolescents - Kenia Rejane de Oliveira Batista; Mona Gizelle Dreger de Oliveira; Carla Fabiane dos Santos Lemos; Josiene de Oliveira Couto; Nara Michelle Moura Soares; Roberto Jeronimo dos Santos Silva (Universidade Federal de Santa Catarina, 2018)
Cardiorespiratory fitness is an important health status indicator. The purpose of this study was to verify the cardiorespiratory fitness according to age group and gender in children and adolescents from Sergipe, Brazil. It is a cross-sectional study with sample consisting of 195 adolescents of both genders with mean age of 11.75 ± 3.0 years. For the characterization of participants, a questionnaire with age and gender identification designed by researchers was used. Subsequently, participants were submitted to anthropometric evaluation in order to estimate the maturational stage by means of the peak height velocity (PHV). The 20-meter back-and-forth test was used to estimate cardiorespiratory fitness. Two-way ANOVA was applied with sample divided into two groups ("up to 13 years" and "above 13 years"). Polynomial contrast was used to identify the type of tendency for cardiorespiratory fitness, and simple contrast for multiple comparisons. All procedures were performed using SPSS version 22.0 software, considering 5% significance level. In the "over 13 years" group, there was a significant effect on the cardiorespiratory capacity behavior according to "gender" [F(1, 45) = 5.54, p = 0.02, r = 0.33] and "age" [F(4.45) = 3.37, p = 0.02, r = 0.48]. The simple contrast identified increased cardiorespiratory fitness behavior in relation to age groups of 15 and 16 year when compared to the age group of 14 years. It was concluded that gender and age positively influence cardiorespiratory fitness from the maturational reference age in the study group.